Bleaching and microstructural effects of low concentration hydrogen peroxide photoactivated with LED/laser system on bovine enamel - Costa, Joatan Lucas de Sousa Gomes [UNESP] (2021)
Background: Tooth whitening protocols with low concentration hydrogen peroxide (HP) appear to minimize the microstructural effect on teeth. In addition, light sources have been used to enhance bleaching efficiency. This study evaluated the color change and microhardness of a protocol with 6% HP photoactivated by LED/laser in comparison with 35% HP. Methods: Twenty bovine incisors were randomized in two groups: 6% HP + LED/laser and 35% HP (n=10). Teeth were submitted to staining using dark tea. Three whitening sessions were carried out according to the manufacturer's instructions. Enamel microhardness (VHN) and color change evaluation (∆L*, ∆a*, ∆b*, ∆E00 [CIEDE2000], and WID) before 24 hours and 7 days after the last whitening session were performed. Two-way repeated ANOVA and Bonferroni post-test was used (α = 0.05). Results: Both groups showed perceptible color changes, being more pronounce for 35% HP. Differences were observed for ∆a*, ∆b* and ∆E00 (p≤0.027), except for ∆L* (p>0.05). Differences were also found in the comparison among the evaluation times within the same group (p≤0.027), except for ∆a* results (p>0.05). WID showed that 35% HP exhibited high whiteness values. Regarding microhardness, the groups did not show significant differences (p>0.05). However, 35% HP showed decreased values after 7 days of the last whitening session compared to the baseline (p≤0.027). Conclusions: 6% HP + LED/laser promoted perceptible color change, but not comparable with 35% HP. No differences on enamel microhardness were observed between the whitening protocols. However, 35% HP showed decreased hardness after 7 days of whitening compared to baseline.